2016
DOI: 10.1093/nar/gkw801
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-coupled changes to chromatin underpin gene silencing by transcriptional interference

Abstract: Long non-coding RNA (lncRNA) transcription into a downstream promoter frequently results in transcriptional interference. However, the mechanism of this repression is not fully understood. We recently showed that drug tolerance in fission yeast Schizosaccharomyces pombe is controlled by lncRNA transcription upstream of the tgp1+ permease gene. Here we demonstrate that transcriptional interference of tgp1+ involves several transcription-coupled chromatin changes mediated by conserved elongation factors Set2, Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 75 publications
1
31
1
Order By: Relevance
“…H3K36me3 is a co-transcriptionally established modification that occurs in regions downstream of active promoters (Xiao et al, 2003;Bannister et al, 2005;Mikkelsen et al, 2007). In yeast, H3K36me3 is associated with a decrease in spurious transcription initiation from within the body of transcribed genes and repression of gene promoters (Hampsey and Reinberg, 2003;Carrozza et al, 2005;Keogh et al, 2005;Houseley et al, 2008;Kim and Buratowski, 2009;Govind et al, 2010;Kim et al, 2012;van Werven et al, 2012;Ard and Allshire, 2016;Chia et al, 2017). We observed an increase in H3K36me3 enrichment downstream of the Adh DIST transcription start site in the two Adh UAS lines in which the abundance of the Adh DIST transcript and the degree of Adh PROX repression were most pronounced: UAS/UAS and UAS/+; GAL4/bal ( Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H3K36me3 is a co-transcriptionally established modification that occurs in regions downstream of active promoters (Xiao et al, 2003;Bannister et al, 2005;Mikkelsen et al, 2007). In yeast, H3K36me3 is associated with a decrease in spurious transcription initiation from within the body of transcribed genes and repression of gene promoters (Hampsey and Reinberg, 2003;Carrozza et al, 2005;Keogh et al, 2005;Houseley et al, 2008;Kim and Buratowski, 2009;Govind et al, 2010;Kim et al, 2012;van Werven et al, 2012;Ard and Allshire, 2016;Chia et al, 2017). We observed an increase in H3K36me3 enrichment downstream of the Adh DIST transcription start site in the two Adh UAS lines in which the abundance of the Adh DIST transcript and the degree of Adh PROX repression were most pronounced: UAS/UAS and UAS/+; GAL4/bal ( Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…These mechanisms are not mutually exclusive and in fact have been shown to act in concert (van Werven et al, 2012;Chia et al, 2017). In the case of chromatin state changes, co-transcriptional histone modifications such as histone 3 lysine 36 trimethylation (H3K36me3) have been associated with nucleosome stabilization and repression of the downstream promoter (Hampsey and Reinberg, 2003;Carrozza et al, 2005;Keogh et al, 2005;Houseley et al, 2008;Kim and Buratowski, 2009;Govind et al, 2010;Kim et al, 2012;van Werven et al, 2012;Ard and Allshire, 2016;Chia et al, 2017). While these studies have been conducted extensively in yeast, the link between H3K36me3 and transcription-coupled repression has been less clear in metazoans.…”
Section: Introductionmentioning
confidence: 99%
“…Examples from yeasts and other eukaryotes have demonstrated that transcription through promoters of protein coding genes exerts repression (Ard et al, 2014;Bumgarner et al, 2009;Latos et al, 2012;Martens et al, 2004;Rom et al, 2019;van Werven et al, 2012). At these loci, chromatin regulators such as facilitator of chromatin transcription (FACT), Set2-dependent deposition of lysine 36 methylation, Set3 mediated histone de-acetylation and others mediate transcriptional repression evoked by lncRNA transcription (Ard and Allshire, 2016;Hainer et al, 2011;Kim et al, 2012;van Werven et al, 2012). Conversely, lncRNA transcription can also stimulate opening of chromatin and promote coding gene transcription, which involves increased histone acetylation and disassembly of nucleosomes locally (Hirota et al, 2008;Takemata et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptional interference is thought to occur when a traversing RNA polymerase elongation complex, arising from one promoter, encounters and displaces a transcription initiation complex, which has formed transiently at a different promoter (Shearwin et al, 2005;Palmer et al, 2011). In some cases, epigenetic changes of transcriptional elongation have been associated with transcriptional interference (Houseley et al, 2008;Hainer et al, 2011;Ard & Allshire, 2016). Transcriptional interference is well characterized in lower eukaryotes with compact genomes where the transcriptional path of one gene runs on into the promoter of another gene (Greger et al, 2000;Martens et al, 2005;Hongay et al, 2006;Petruk et al, 2006;Gummalla et al, 2012;Ard et al, 2014).…”
Section: Introductionmentioning
confidence: 99%